Emotional reactions in moral decision-making are influenced by empathy and alexithymia. (4th March 2018) - Cecchetto, Cinzia; Korb, Sebastian; Rumiati, Raffaella Ida; Aiello, Marilena
ABSTRACT: The role of emotional processes in driving moral choices remains debated. In particular, diminished emotional processing and reduced empathy have been associated with unusual high rates of utilitarian responses in moral judgments while, to date, the effects of diminished emotional processing and empathy on moral decision-making have been only partially considered. In this study, we investigated the influence of empathy and alexithymia on behavior and emotional responses while participants performed a moral decision task. Self-report (valence and arousal ratings) and physiological (skin conductance and heart rate) measures were collected during the task. Results showed that empathy and alexithymia shaped emotional reactions to moral decisions but did not bias moral choices. The more empathic the participants, the more dilemmas were perceived as unpleasant and arousing, and the greater the increase in skin conductance. Conversely, alexithymia was characterized by a reduced physiological activation during moral decisions, but normal self-report ratings. Heart rate was not modulated by empathy or alexithymia. These results add new evidence to the field of moral decision showing that empathy and alexithymia modulate emotional reactions to moral decision.